MtLAX2, a Functional Homologue of the Arabidopsis Auxin Influx Transporter AUX1, Is Required for Nodule Organogenesis . Issue 1 (31st March 2017) - Roy, Sonali; Robson, Fran; Lilley, Jodi; Liu, Cheng-Wu; Cheng, Xiaofei; Wen, Jiangqi; Walker, Simon; Sun, Jongho; Cousins, Donna; Bone, Caitlin; Bennett, Malcolm J.; Downie, J. Allan; et al.
Abstract : Genetic and molecular biological tools were used to show that MtLAX2 is required for not only lateral root formation but also nodulation, in Medicago truncatula. Abstract: Most legume plants can form nodules, specialized lateral organs that form on roots, and house nitrogen-fixing bacteria collectively called rhizobia. The uptake of the phytohormone auxin into cells is known to be crucial for development of lateral roots. To test the role of auxin influx in nodulation we used the auxin influx inhibitors 1-naphthoxyacetic acid (1-NOA ) and 2-NOA, which we found reduced nodulation of Medicago truncatula. This suggested the possible involvement of the AUX/LAX family of auxin influx transporters in nodulation. Gene expression studies identified MtLAX2, a paralogue of Arabidopsis ( Arabidopsis thaliana ) AUX1, as being induced at early stages of nodule development. MtLAX2 is expressed in nodule primordia, the vasculature of developing nodules, and at the apex of mature nodules. The MtLAX2 promoter contains several auxin response elements, and treatment with indole-acetic acid strongly induces MtLAX2 expression in roots. mtlax2 mutants displayed root phenotypes similar to Arabidopsis aux1 mutants, including altered root gravitropism, fewer lateral roots, shorter root hairs, and auxin resistance. In addition, the activity of the synthetic DR5-GUS auxin reporter was strongly reduced in mtlax2 roots. Following inoculation with rhizobia, mtlax2 roots developed fewer nodules, had decreased DR5-GUS activity associated with infection sites, and had decreased expression of the early auxin responsive gene ARF16a . Our data indicate that MtLAX2 is a functional analog of Arabidopsis AUX1 and is required for the accumulation of auxin during nodule formation in tissues underlying sites of rhizobial infection.